Elaboración de un proceso de fútbol y su impacto psicomotriz para las adolescentes del colegio Antonio José de Sucre, del canto Santa Rosa en el periodo 2013-2014. - Castillo Olaya, Patricia Gieleny (2013)
In chapter one contains the definition of the problem, what will we aim to find the information relevant and necessary to develop this research work.